The Effectiveness of The Implementation of SPIP and SIMDA Its Impact Against The Quality of Financial Statements - Galih Raspati; Andi Riyanto (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2021)
ABSTRACTThe phenomenon of government financial reports that have not received an unqualified opinion because they have not presented financial information that is following applicable standards and is not transparent and accountable for the management of regional finances, makes the level of trust of users of financial statements doubt the various information presented. The demand for clean governance is also a strong foundation so that the bureaucratic apparatus is able to present quality financial statements. This study aims to understand the effectiveness of the application of the Government Internal Control System (SPIP) and the Regional Management Information System (SIMDA) currently being applied and its impact on the quality of financial statements. The research method used was a survey method. Then the data is collected from the results of questionnaires, interviews and literature studies. Data analysis is descriptive and verification. The results showed that SPIP and SIMDA had a significant impact on the quality of financial statements in Cireunghas District, Sukabumi District.    Keywords: financial statements, quality, SIMDA, SPIP